The adaptation of the live PDC darts event during the COVID-19 lockdown - Davis, L. (Managing Sport and Leisure, 2020)
The COVID-19 outbreak led to the cancellation of sporting events across the world in the spring of 2020 and forced billions of people across the globe to stay home and self-isolate for a number of months. One of the first sports to reposition and adapt their product during the global lockdown in March/April 2020 was professional darts. The Professional Darts Corporation (PDC) took an opportunity to promote their version of darts via an elite online home tournament, the PDC Home Tour, in a vast sports market craving live sporting action. This commentary provides an understanding of how professional darts, a sport that has relied on fan interaction within multi-purpose arenas at live events, attempted to move online to a home-based tournament for a temporary period to fill a sporting void. The commentary discusses the reaction to the tournaments held by the PDC and MODUS and issues encountered, before exploring the reasons for the tournaments being held during the primary global lockdown. As a niche sport, it is hoped that this commentary can provide some insight into the contemporary sport of professional darts, a sport rarely discussed in the scholarly field of sport and leisure.